2018
DOI: 10.1021/acscatal.7b01030
|View full text |Cite
|
Sign up to set email alerts
|

Speciation and Dynamics in the [Co4V2W18O68]10–/Co(II)aq/CoOx Catalytic Water Oxidation System

Abstract: Our group reported that the polyoxometalate Na 10 [Co 4 V 2 W 18 O 68 ]•26H 2 O (Co 4 V 2 ) is an active water oxidation catalyst and provided characterization of this system (J. Am. Chem. Soc. 2014, 136 (26), 9268). Two recent publications called into question the stability of Co 4 V 2 , one noting the miss-assignment of a 51 V NMR peak (Inorg. Chem. 2016, 55 (11), 5343) and another providing additional stability studies (ACS Catal., 2017, 7 (1), 7). We report here solution studies that further clarify stabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 43 publications
1
11
0
Order By: Relevance
“…Very recently, the Ag + salt of Co 189,19051,52 Recent vanadium NMR solution studies on the NMR/Co II aq/CoO x system describe a complex speciation behavior in solution, making the identification of the various equilibrating aqueous active catalysts in the system is a challenging task. 191 Despite several advances, the large catalytic difference between Co 4 V 2 and Co 4 P 2 called for examining the significance of substituting phosphorus centers in Co 4 P 2 with vanadium. A thorough DFT study on the OER mechanism for Co 4 P 2 suggested that the O-O bond formation takes place from a Co 3+ -oxyl radical through the WNA attack pathway.…”
Section: Cobalt-based Pom Wocsmentioning
confidence: 99%
“…Very recently, the Ag + salt of Co 189,19051,52 Recent vanadium NMR solution studies on the NMR/Co II aq/CoO x system describe a complex speciation behavior in solution, making the identification of the various equilibrating aqueous active catalysts in the system is a challenging task. 191 Despite several advances, the large catalytic difference between Co 4 V 2 and Co 4 P 2 called for examining the significance of substituting phosphorus centers in Co 4 P 2 with vanadium. A thorough DFT study on the OER mechanism for Co 4 P 2 suggested that the O-O bond formation takes place from a Co 3+ -oxyl radical through the WNA attack pathway.…”
Section: Cobalt-based Pom Wocsmentioning
confidence: 99%
“…30,31 This gives rise to ongoing and challenging speciation studies. 32 performance of oxide WOCs. These ndings show that synthetic methods and underlying mechanisms 36 are an important step in WOC optimization, [37][38][39] and that a certain extent of preorganization of the metal centers in the precursor is benecial for higher catalytic activity.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the encapsulation of POMs in highly porous MOFs, POMs may also be incorporated as redox catalytic centers through robust coordination bonds, while organic linkers may efficiently facilitate the proton coupled electron transfer. , The extension of the POMs species has strongly motivated the interest in POMs chemistry due to the their high lattice energy. For this purpose, the introduction of heteroatoms into a POM structure may be a feasible method to enrich the POMs’ topology structure. Notably, the design of a 2D POM layer with suitable cations and extension into MOFs are promising for this device construction. , Once the stability of the 2D POM layer based MOFs has been established, they may have important consequences for applications in photocatalytic water splitting.…”
Section: Introductionmentioning
confidence: 99%